THE LEGAL STUDY OF NORMS OF CORNEAL DONOR REGULATION IN INDONESIA - Nyoman, Yenny Khristiawati; Yulianto, Yulianto (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
This research is determined to analyze about Indonesian citizen human rights and constitutional rights as a corneal transplant donors and recipients, also to analyze legal protection for Indonesian citizens. This research is a normative juridical method which is research that discusses about principles in law science, to look for solutions or legal issues to identify the basic meanings of rights and obligations, legal events, legal relations, and legal objects. Using a statute approach, a conceptual approach, and a comparative approach. Corneal donor and transplantation in Indonesia is a human right that must be protected and has been regulated in Article 25 of the United Nations Declaration of Human Rights and are also emphasized in Article 12 of the International Convention on Economic Social and Cultural Rights. Meanwhile the constitutional rights of Indonesian citizens as donors and recipients of corneal transplants have actually been stipulated in Article 28 H of the 1945 Constitution jo, Article 9, Article 64 Paragraph 1 and Paragraph 2 of the Health Law No. 36 of 2009, Article 28 of the Republic of Indonesia Government Regulation Number 53 of 2021, but these regulatory norms still do not provide optimal guarantees for both donors and recipients of corneal transplants.